PENERAPAN AKAD AS SALAM DALAM JUAL BELI BATU BATA MENURUT PERSPEKTIF EKONOMI ISLAM ( Studi Kasus Desa Paloh Gadeng Kecamatan Dewantara Kabupaten Aceh Utara)” - Sri Nazarni (LPPM, 2021)
This study aimed to determine the application of the contract As-salam to buying and selling bricks and knowing the Islamic economic review of the buying and selling of bricks. The method used was a descriptive qualitative method using data collection techniques through observation, interviews, and documentation. The data in this study came from several groups of people in Paloh Gadeng, Dewantara subdistrict, North Aceh Regency, namely: sellers and buyers, brick laborers, community leaders. The findings showed that most of the brick sellers in Paloh Gadeng Village had implemented the As-salam contract to facilitate transactions between the seller and the buyer in selling bricks by paying for the goods ordered in advance at the beginning of the transaction, and then the seller produced the order from the buyer. However, some sellers had not implemented the As-salam contract and made payments in full at the beginning of the transaction and immediately took orders for goods without waiting for the production process.